PLAYFUL RESOURCES IN THE DEVELOPMENT OF READING ON CHILDREN WITH AUTISTIC SPECTRUM DISORDER. - Oliveira Soares, Mayla (Revista Gênero e Interdisciplinaridade, 2022)
The present study is outlined on the topic student with Autism Spectrum Disorder and reading practice. In this way, it seeks as an objective to elucidate the main challenges and possibilities for reading from the use of playful resources. It seeks, in parallel, to contribute with the conceptual aspects and outlining possible actions of educators and possible pedagogical strategies that contribute to the teaching and learning process. To achieve the proposed objectives, the present research appropriated a bibliographic, qualitative study, searching through the existing literature in the main databases, to elucidate the proposed aspects. As a result, the literature has shown that the school is faced with challenges mainly in the aspects of teacher preparation and educational strategies. As possibilities, it has mainly highlighted the work with playful resources, whether through games, games, paintings, among others, which allows the student with ASD, auditory aspects that are fundamental for learning, especially reading. It is concluded that playful resources have been shown as a highly effective methodology in the schooling process of the autistic student, contributing to the most diverse fields, which are essential for reading, writing and the integral development of this student.